2018
DOI: 10.3329/bjar.v43i1.36186
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and heterosis study in maize (Zea mays L.) Hybrids at different environments in Bangladesh

Abstract: The aim of this study was to isolate superior inbred lines and better combining parents for suitable hybrids and to determine percent of heterosis using standard commercial checks in a 7 × 7 diallel analysis excluding reciprocals over five environments. The mean sum of square obtained from combined analysis of variance showed the presence of genetic variability among the crosses, environment and crosses × environment interaction for all of the characters under study. The variances for general combining ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 8 publications
7
17
0
Order By: Relevance
“…Hybrids play crucial role in maize production increment (Aslam, Sohail, Maqbool, Ahmad, & Shahzad, 2017;Karim, Ahmed, Akhi, Talukder, & Mujahidi, 2018) and food security. Hybrid maize varieties development needs selection of appropriate parents (inbred lines) which is the covert of success in hybrid maize development.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrids play crucial role in maize production increment (Aslam, Sohail, Maqbool, Ahmad, & Shahzad, 2017;Karim, Ahmed, Akhi, Talukder, & Mujahidi, 2018) and food security. Hybrid maize varieties development needs selection of appropriate parents (inbred lines) which is the covert of success in hybrid maize development.…”
Section: Introductionmentioning
confidence: 99%
“…The percent heterosis for grain yield varied from -85.76 to 10.83% (Table 05). Moreover, Karim et al, (2018), Talukder et al, (2016) and Begum et al, (2018) found 5.25%, 12.53 % and 9.9% significant positive heterosis in their studied materials, respectively. Among the 28 F1, three crosses revealed positive heterosis for grain yield.…”
mentioning
confidence: 80%
“…There are several studies regarding diallel designs in maize breeding [ 14 , 48 50 ], but only a few of them performed spatial analyses, mainly diallel MET analyses [ 51 ]. In addition, the use of spatial analyses has been increasing in recent years [ 43 , 45 , 52 57 ].…”
Section: Introductionmentioning
confidence: 99%